FACTORS AFFECTING THE INCIDENCE OF VAGINAL DISCHARGE AMONG FEMALE INMATES OF CHILDBEARING AGE IN CLASS IIB WOMEN'S PRISON, PADANG - Dian Furwasyih; Maidelwita, Yani; Shofiah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Vaginal discharge is an indicator of an abnormal health condition in the body, characterized by the release of a fluid, other than blood, from the female reproductive organ. In July 2023, two female inmates at Class IIB Women's Prison in Padang reported experiencing vaginal discharge accompanied by itching and an unpleasant odor. They received medical treatment at the prison clinic. The incidence of vaginal discharge in West Sumatra is approximately 3.51%. This study aims to identify the factors influencing the occurrence of vaginal discharge among female inmates of childbearing age. A quantitative research approach was used, employing a cross-sectional design and a total sampling technique, with 57 respondents. The variables examined include knowledge level, access to reproductive health information, and personal hygiene behavior during menstruation. Data analysis was conducted using univariate and bivariate methods with chi-square tests. The findings revealed that 43.9% of respondents experienced vaginal discharge, 71.9% had a low level of knowledge, 57.9% faced difficulties in accessing reproductive health information, and 56.1% exhibited poor personal hygiene behavior during menstruation. There was a significant relationship between knowledge level and the incidence of vaginal discharge (p=0.045), as well as between personal hygiene behavior and vaginal discharge occurrence (p=0.037). However, no significant correlation was found between access to reproductive health information and vaginal discharge (p=0.426). This study concludes that improving reproductive health education and providing adequate hygiene facilities in the prison environment are crucial steps in reducing the incidence of vaginal discharge among female inmates.